Relevansi Pendekatan Kultural Linguistik Dengan Pluralitas Agama di Indonesia - Eko Kurniawan Wibowo (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2021)
Abstract: Indonesia is a plural state. Not only ethnicity, race and group, but also plural in religion where religious plurality is also a separate problem. The problem of religious plurality raises many problems that cause friction in life together. The linguistic cultural approach offered by George A. Lindbeck provides an alternative for relations for believers of diverse religion. Lindbeck's offer consistently provides space for the identity of the believer's faith without having to equate with the faith of other religions. Likewise, consistently provide space for appreciation for other religious faiths. Abstrak: Indonesia merupakan Negara yang sangat plural. Tidak hanya suku, ras dan golongan tetapi plural juga dalam agama dimana pluralitas agama juga menjadi persolan tersendiri. Persoalan pluralitas agama tersebut menimbulkan banyak permasalahan yang menimbulkan gesekan dalam kehidupan bersama. Pendekatan kultural linguistik yang ditawarkan George A Lindbeck memberikan alternatif bagi relasi bagi pemeluk agama yang sangat majemuk tersebut. Tawaran Lindbeck tersebut tetap memberikan ruang bagi identitas iman umat, tanpa harus menyamakan iman pribadi dengan iman liyan. Pun, tetap memberikan ruang apresiasi bagi iman agama yang lain.